Invisible monsters - Palahniuk, Chuck (Vintage, 1999)
The career of a model ends when she is disfigured in an accident. Suspecting the accident was the work of her ex-boyfriend and his new girlfriend, she takes revenge by slipping him a drug to grow breasts.